1984
DOI: 10.1128/aac.26.2.139
|View full text |Cite
|
Sign up to set email alerts
|

New polymeric biocides: synthesis and antibacterial activities of polycations with pendant biguanide groups

Abstract: Acrylate monomers with pendant biguanide groups were successfully synthesized, and their homopolymers and copolymers were prepared with acrylamide. These cationic disinfectants of polymeric forms exhibited high antibacterial activity against gram-positive bacteria, whereas they were less active against gram-negative bacteria. It was found that the activity of the polymeric disinfectants was much higher than that of the monomeric species, and the difference in activity between the polymers and the monomers was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(144 citation statements)
references
References 12 publications
2
142
0
Order By: Relevance
“…centrifuged at 3000 x g for 10 min at 4°C, washed 3 times in PBS then resuspended in 1 ml PBS. 50 µl from each time point was resuspended in 10 ml PBS at 2.5 x 10 6 CFU/ml and another 50 µl was resuspended in 10 ml of 1 mg/ml trypan blue (Beckman Coulter, CA, USA) in PBS at 2.5 x 10 6 CFU/ml 37 . Samples were incubated at ambient temperature for at least 30 min, but not more than 6 hours to ensure bacterial survival.…”
Section: Synthesis Of 50 % Quaternised Pdmaemamentioning
confidence: 99%
See 1 more Smart Citation
“…centrifuged at 3000 x g for 10 min at 4°C, washed 3 times in PBS then resuspended in 1 ml PBS. 50 µl from each time point was resuspended in 10 ml PBS at 2.5 x 10 6 CFU/ml and another 50 µl was resuspended in 10 ml of 1 mg/ml trypan blue (Beckman Coulter, CA, USA) in PBS at 2.5 x 10 6 CFU/ml 37 . Samples were incubated at ambient temperature for at least 30 min, but not more than 6 hours to ensure bacterial survival.…”
Section: Synthesis Of 50 % Quaternised Pdmaemamentioning
confidence: 99%
“…The mode of action of cationic biocides has been suggested to progress as follows: (1) adsorption onto the bacterial cell surface, (2) diffusion through the cell wall, (3) binding to the cytoplasmic membrane, (4) disruption of the cytoplasmic membrane, (5) release of cell cytoplasmic constituents and (6) cell death 37 . pDMAEMA may work in a similar manner by adsorbing to the cell surface through electrostatic interactions and disrupting the cytoplasmic membrane through hydrophobic interactions 28,30 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, we reported that in a clean system where there are no interfering materials such as negatively charged macromolecules, polycations having biguanide units or quaternary ammonium salts exhibit much higher antibacterial activity than the monomeric analogs (4,5). In view of the fact that many properties of polymers depend strongly on their molecular weights (MW) and MW distributions, it is reasonable to expect that the antibacterial activity of such polycations is MW dependent.…”
mentioning
confidence: 99%
“…Biguanides of the polyhexamethylene biguanide hydrochloride type were originally developed as surface disinfectant in the food and beverage industry. Its antimicrobial action is based on the binding of the cationic molecules to the anionically charged bacteria, leading to membrane rupture and denaturation of proteins [18][19][20]. Complete destruction of S. aureus was found after 5-10 min of exposure to 0.2% biguanide solution [21].…”
Section: Discussionmentioning
confidence: 99%